Estimation the Volume of Water Erosion for Jadida Valley Basin in Erbil, Northern Iraq - Asaad Al-Hussein (Iraqi Geological Journal, 2022)
This study examined the potential of predicting the volume of water erosion using the erosion probability model, which is one of the most widely used methods for assessing soil degradation within drainage basins. This research aimed to determine the surface areas subjected to erosion and the resulting sediment quantities during one year, after demonstrating the impact of various natural conditions on the basin using remote sensing technology, which was represented by modern satellite visuals with the introduction and analysis of these visuals in the context of geographic information systems, as well as the application of a set of mathematical equations.This study shows that locations with high topography are always subjected to torrential waters, resulting in significant erosion, as opposed to plain areas, where erosion is weak or non-existent. The amount of soil lost in the basin ranged from 0.056–6900 m3/km2/year, and also included places with minimal erosion (26.705%) While weak erosion was found in 43.890% of the entire to the basin, moderate erosion was found in 20.929%, severe erosion was found in 5.762% and very severe erosion was found in 2.713% which includes places with steep slopes and no vegetation. The annual average of water erosion in the basin is projected to be 797.434 m3/km2/year, with an annual volume of eroded soil in the basin of around 321129.861 m3/year, necessitating the development of a plan to manage drift and reduce the danger of water erosion in the basin.